A normalized quality of life approach for regulatory approval of medical devices - Leuchter Matthias; Philipp Mark; Siewert Stefan; Schafmayer Clemens; Schmitz Klaus-Peter; Kaule Sebastian (Current Directions in Biomedical Engineering)
Patient-reported outcomes (PROs) are used in clinical trials to provide valuable evidence on the impact of treatment on patients’ symptoms, function and quality of life. High-quality PRO data from trials can inform shared decisionmaking, regulatory and economic analyses and health policy. The heterogeneity between the patient groups and the associated differences in morbidity and quality of life can be taken into account by standardization to the general population. As a result, our study shows that despite the retrospective design with the corresponding level of evidence, mesh repair of a ventral hernia leads to an equivalent result compared to tissue hernia surgery.